Validation of the French Version of the MacArthur Competence Assessment Tool for Treatment (MacCAT-T) in a French Sample of Individuals with Schizophrenia: Validation de la version française de l'instrument d'évaluation des compétences MacArthur-traitement (MacCAT-T) dans un échantillon français de personnes souffrant de schizophrénie. (April 2021) - Raffard, Stéphane; Lebrun, Cindy; Laraki, Yasmine; Capdevielle, Delphine
Background: Assessing an individual's capacity to consent to treatment is a complex and challenging task for psychiatrists and health-care professionals. Diminished capacity to consent to pharmacological treatment is a common concern in individuals with schizophrenia. The MacArthur Competence Assessment Tool for Treatment (MacCAT-T) is the most common tool used in individuals with schizophrenia to evaluate the decision-making abilities for judgments about competence to consent to treatment. This instrument assesses patients' competence to make treatment decisions by examining their capacities in 4 areas: understanding information relevant to their condition and the recommended treatment, reasoning about the potential risks and benefits of their choices, appreciating the nature of their situation and the consequences of their choices, and expressing a choice. Despite its importance, there is no French version of this scale. Furthermore, its factor structure has never been explored, although validated measures are strongly needed to further detect deficits in patients' decision-making abilities. The goal of this study was thus to empirically validate a French version of the MacCAT-T in a French sample of individuals with schizophrenia. Method: In this cross-sectional study, we included 125 inpatients with a diagnosis of schizophrenia from the University Department of Adult Psychiatry in Montpellier. The MacCAT-T was administered to patients by a trained psychologist. Patients were also assessed for severity of symptoms, insight into illness, and depressive and anxiety symptoms. Inter-rater reliability and psychometric properties including internal consistency, construct validity, and discriminant and divergent validity were also investigated. Results: The MacCAT-T's internal consistency was high (Cronbach α of 0.91). A high degree of inter-rater reliability was found for all the areas of the MacCAT-T (intraclass correlation coefficient range, 0.92 to 0.98). Exploratory factor analysis revealed a 2-factor model. The factor analysis explained 50.03% of the total score variation. Component 1 included all subparts of "understanding." Component 2 included all subparts of "appreciation" and "reasoning" and was therefore labeled "reflexivity." After Bonferroni corrections, decision-making capacity was positively associated with insight and the severity of psychotic symptoms but not with sociodemographic variables except for education. Conclusions: The MacCAT-T demonstrated a high degree of inter-rater reliability and strong psychometric properties. The French version of the MacCAT-T is a valid instrument to assess the decision-making capacity to consent to treatment in a French sample of individuals with schizophrenia.